2021
DOI: 10.1253/circrep.cr-20-0070
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Cutting Balloon With an Adequate Balloon-to-Artery Ratio for Fracturing Calcification While Preventing Perforation

Abstract: Background: The appropriate balloon-to-artery ratio (BAR) for cutting balloons (CBs), to expand calcified lesions without increasing the risk of coronary artery perforation is unknown. This study investigated the effects of BAR on stress levels in the calcification and at the borders of the coronary artery adjacent to the calcification to determine an appropriate BAR. Methods and Results: A custom-designed folding process of the CB model was developed. The CB models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Elegant simulation model has clearly underlined that secured atherotomes amplify force in calcium, thus generating a higher stress level in calcifications compared with NC balloon; moreover, CB distinctly reduces the stress levels at the border of the artery adjacent to the calcification compared with conventional balloons potentially reducing the rate of flow‐limiting dissections 13 . A possible alternative to CB in CAC is represented by intravascular lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant simulation model has clearly underlined that secured atherotomes amplify force in calcium, thus generating a higher stress level in calcifications compared with NC balloon; moreover, CB distinctly reduces the stress levels at the border of the artery adjacent to the calcification compared with conventional balloons potentially reducing the rate of flow‐limiting dissections 13 . A possible alternative to CB in CAC is represented by intravascular lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that, for severely calcified FP lesions assessed by IVUS, a preballoon dilatation diameter ≥1.9 mm eter is a known factor contributing to sufficient vessel preparation in coronary lesions with calcification. 13,14 In this study, the factor contributing to sufficient vessel preparation for severely calcified FP lesion sites was the preballoon dilatation diameter, and the cutoff value was 1.9 mm for severely calcified FP lesion sites (AUC, 0.80; 95% CI, 0.71-0.89; sensitivity, 74%; specificity, 76%) (Figure 3). Torii et al reported that calcification associated with lowerextremity arteries has various patterns and is thicker than that associated with coronary artery lesion.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, adequate plaque modification prior to stent implantation is critical for calcified lesions. The cutting balloon, which includes 3 or 4 radially directed micro-surgical metal blades on the balloon surface, has been used to create incisions in the calcified plaque and expand narrow lesions [ 16 ]. In the present case, inflation of the cutting balloon within the calcified lesion likely led to the dissection into the media with extension into the medial space without re-entry and the semilunar intramural hematoma.…”
Section: Discussionmentioning
confidence: 99%